2006
DOI: 10.1152/jn.01289.2005
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cortically Related Intermuscular Coherence Accompanying Improvements in Locomotor Skills in Incomplete Spinal Cord Injury

Abstract: . Changes in cortically related intermuscular coherence accompanying improvements in locomotor skills in incomplete spinal cord injury. J Neurophysiol 95: 2580 -2589, 2006. First published January 11, 2006 doi:10.1152/jn.01289.2005. In human spinal cord injury, the neuronal mechanisms mediating the improvement of locomotor function in response to intensive treadmill training are not well understood. In this study, we examined if such recovery is mediated, in part, by increases in residual corticospinal drive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
137
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(145 citation statements)
references
References 35 publications
6
137
1
1
Order By: Relevance
“…This is not the first report of postintervention and specifically post treadmill training effects on corticomotor excitability using TMS in people with neuropathology. Changes in corticomotor excitability and associated improvements in walking function were found after intensive treadmill training both in people with spinal cord injury 57,58 and stroke. 59 However, to our knowledge, this is the first demonstration of exercise-induced changes in corticomotor excitability using TMS in individuals with PD, a progressive neurologic disorder.…”
Section: Discussionmentioning
confidence: 98%
“…This is not the first report of postintervention and specifically post treadmill training effects on corticomotor excitability using TMS in people with neuropathology. Changes in corticomotor excitability and associated improvements in walking function were found after intensive treadmill training both in people with spinal cord injury 57,58 and stroke. 59 However, to our knowledge, this is the first demonstration of exercise-induced changes in corticomotor excitability using TMS in individuals with PD, a progressive neurologic disorder.…”
Section: Discussionmentioning
confidence: 98%
“…Care should be taken when comparing the area of coherence from studies or conditions with different amounts of segments available and/or used in the analysis. Especially when the area of coherence is used to assess the effect of rehabilitation interventions, there is a considerable chance that individuals are able to walk for a longer time post compared to pre intervention (Norton and Gorassini, 2006). The larger number of available segments for analysis would introduce a bias towards finding an increase in the area of coherence.…”
Section: Effect Of Processing Settings and Walking Conditionmentioning
confidence: 99%
“…Early studies explored the cortical involvement in the control of walking (Hansen et al, 2001;Halliday et al, 2003;Petersen et al, 2010). More clinically oriented studies showed that the EMG-EMG coherence in the beta band in patients with motor deficits resulting from stroke (Bo Nielsen et al, 2008) or spinal cord injury (Barthélemy et al, 2010;Hansen et al, 2005;Norton and Gorassini, 2006) is decreased. These decreases indicate that beta-band EMG-EMG coherence depends largely on the integrity of the corticospinal tract.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations